Determinants of Trust in Higher Education - I. S. Kuznetsov (Высшее образование в России)
The article addresses the factors that influence students’ trust in the teachers, faculty administration and university administration. Establishing trusting relationships at the university leads to a number of positive effects: for example, it facilitates cooperation between members of educational organization, making them more united, open to communication and motivated; it is a prerequisite for academic excellence, high-quality higher education and loyalty. This is the reason of the researchers’ interest to this topic. However, the factors influencing students’ trust in teachers and university management have yet to be defined. This paper examines the individual, socio-economic and institutional characteristics of student trust. The emphasis is placed on subjective factors – the perception and assessment by young people of what happens with them in the learning process. It is shown that students’ trust in the teachers and university management is positively correlated with their justified expectations (satisfaction), regarding higher education, and negatively correlated with the course of study. The influence of gender is significant when students trust in the administration of the faculty, while the influence of family income is significant when they trust in the administration of the university. Moreover, the last two factors are regionally specific: their effects are significant only for the trust of students studying at Moscow and St. Petersburg universities.